O controle externo das polícias pelo Ministério Público: uma análise sociológica - Paulo, Bruno Giovannini de (2025)
This dissertation examined the constitutional mandate of external oversight of the police by the Public Prosecutor’s Office in Brazil (CEAP). Its objective was to analyze and understand how this oversight has been implemented in practice, as well as to investigate whether the violence and selectivity identified in the police's conflict management activities have been addressed by prosecutorial action. The theoretical framework was based on the concept of the field of crime control developed by Garland (2008) and Sinhoretto (2020), along with the strategies identified by Sinhoretto that traverse this field. The methodology employed was qualitative in nature, grounded in the analysis of official documents and interviews. The empirical focus encompassed two geographically proximate regions located in different federative units—Triângulo Mineiro and Noroeste Paulista—which enabled a comparative understanding of distinct organizational contexts. The findings revealed a range of challenges to the effective exercise of CEAP, including lack of institutional infrastructure, resistance from police corporations, and the individual and institutional interests of Public Prosecutor’s Office members. Based on these findings, the research proposed several measures to enhance CEAP: the establishment of specialized prosecutorial units with functional autonomy; a revision of the performance metrics of the Public Prosecutor’s Office; a more assertive role for the National Council of the Public Prosecutor’s Office; expanded civil society participation; reform of prosecutors’ training; the transfer of jurisdiction over crimes committed by military police officers to the ordinary judiciary; and the gradual demilitarization of law enforcement agencies. Finally, the study acknowledged that, despite being marked by contradictions and institutional resistance, the field of external police oversight presents fissures that may be strategically leveraged by actors committed to the protection of fundamental rights.